As incubadoras tecnológicas de cooperativas populares e a produção do conhecimento: uma análise crítica do conhecimento científico no âmbito das ITCPS - Ribeiro, Lourenca Santiago (2021)
Among the objectives of the Technological Incubators of Popular Cooperatives (ITCPs) are the assistance of Solidarity Economic Enterprises and the production and dissemination of knowledge about the field called Solidarity Economy. They are characterized as counter-hegemonic niches within a hegemonic institution by nature. That said, it is reported that the general objective of this thesis was to carry out a critical analysis of the scientific knowledge produced within the scope of ITCPs. For that, a descriptive research with a qualitative and quantitative approach was carried out. The methodology used was bibliographic and documentary research, and the instrument or data collection strategy was document analysis, which involved the analysis of 66 articles published in the period from 2012 to 2017 by teachers and technicians members of 15 ITCPs linked to the Network of ITCPs and who carried out the last two public notices of the National Incubator Program for Popular Cooperatives – PRONINC. The analysis of the articles allowed the identification of data and information related to: authors, themes, keywords, scope, objectives, theoretical framework, method, methodology, procedure, instruments, data collection strategies and complementary aspects. At the end of the data were systematized and underwent an interpretive descriptive analysis. Among the results of deaths, it is found that the knowledge developed under the ITCPs is predominantly produced by women, however this is not reflected in either the form or the content, such as in conducting studies on gender or related topics. It is knowledge produced by professional researchers with a Master’s or Doctoral degree from different areas of knowledge. Considering the themes studied, the scope of research and the objectives of the articles, it is an endogenous knowledge, which correlates theory and practice, produced based on local problems. It is critical knowledge, it dialogues with other knowledge, developed in dialogue with socially excluded people and on topics that are not of interest to modern science, from capitalism. The theoretical framework used is predominantly critical. Regarding the methodological aspects of the analyzed articles, it was observed that many authors are not concerned with the characterization of the research, nor with the description of the design or methodological path used. With regard to methodological aspects, qualitative research predominates, the most used data collection strategies are observation and interviewing. Among the issues identified and considered contradictory, considering the ideas of the solidarity economy and the characteristics of knowledge in the counter-hegemonic perspective, the following stand out: the disciplinary nature of knowledge production, the absence of workers among the authors. It does not establish connections with other anti-system movements, such as lgbtqia+, feminism, housing and others. And finally, there was a lack of articles that dealt with topics relevant to the advancement of the Solidarity Economy field, such as: credit, solidarity finance, Social Technology, gender, sustainability, well-being, and legal education of EES, for example.